Evaluation of The Development of Corporate Social Responsibility (CSR) Programs PT PERTAMINA (PERSERO) - Faatin, Faradiba Nurjannah; Ekasari, Kurnia; Wahyuni, Hesti (PT. EQUATOR SINAR AKADEMIA, 2024)
This study aims to evaluate the development of PT Pertamina (Persero) corporate social responsibility program. Secondary data were used in this research. The process of gathering data and doing content analysis involves comprehending CSR activities and locating the GRI index in PT Pertamina's sustainability report (Persero). The results of this study are that in 2018, 2020, and 2021, PT Pertamina (Persero) focused more on GRI 200 and less on GRI 400 disclosure. In 2019, the company focused on GRI 300 on the environment and still lacked the level of social disclosure. Then, in 2022, the company made many disclosures on GRI 300, namely environmental aspects, and less on GRI 200 disclosures, namely economic aspects. Overall, over five periods, disclosure rates in the GRI 200 environmental category tended to be higher than those in the other two categories at 69%. In the economic category, there was a disclosure rate of 68%, and in the social category, there was 55% related to disclosure.